2015
DOI: 10.1371/journal.pone.0142971
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Labellum Pattern Variation in a Sexually Deceptive Orchid (Ophrys heldreichii): Evidence of Individual Signature Learning Effects

Abstract: Mimicking female insects to attract male pollinators is an important strategy in sexually deceptive orchids of the genus Ophrys, and some species possess flowers with conspicuous labellum patterns. The function of the variation of the patterns remains unresolved, with suggestions that these enhance pollinator communication. We investigated the possible function of the labellum pattern in Ophrys heldreichii, an orchid species in which the conspicuous and complex labellum pattern contrasts with a dark background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 75 publications
2
31
0
Order By: Relevance
“…Factors maintaining high levels of phenotypic variation in deceptive systems have been investigated in several studies (see Juillet & Scopece, 2010 and references therein), particularly after Heinrich ’s (1975) proposal that phenotypic variability decreases pollinator avoidance learning, thereby increasing orchid reproductive success. This hypothesis has also been recently suggested by Stejskal et al (2015) to explain variation in the labellum patterns of a sexually-deceptive orchid. However, Juillet & Scopece (2010) showed that all attempts to identify a reproductive advantage linked with phenotypic variation in food-deceptive species were non-significant or indicated a lower reproductive success thus underlining the need of more studies to support or discard this hypothesis.…”
Section: Introductionsupporting
confidence: 54%
“…Factors maintaining high levels of phenotypic variation in deceptive systems have been investigated in several studies (see Juillet & Scopece, 2010 and references therein), particularly after Heinrich ’s (1975) proposal that phenotypic variability decreases pollinator avoidance learning, thereby increasing orchid reproductive success. This hypothesis has also been recently suggested by Stejskal et al (2015) to explain variation in the labellum patterns of a sexually-deceptive orchid. However, Juillet & Scopece (2010) showed that all attempts to identify a reproductive advantage linked with phenotypic variation in food-deceptive species were non-significant or indicated a lower reproductive success thus underlining the need of more studies to support or discard this hypothesis.…”
Section: Introductionsupporting
confidence: 54%
“…The wasp was then allowed to approach the apparatus again to make a novel choice. This method was developed to promote learning of complex patterns including faces in free flying honeybees (Avarguès-Weber, Portelli, et al, 2010;Dyer et al, 2005Dyer & Vuong, 2008;Stejskal et al, 2015). This procedure avoided positional learning of the rewarding stimuli and ensured that the stimuli could be visually inspected between choices.…”
Section: Training Proceduresmentioning
confidence: 99%
“…The impressive visual learning abilities by honeybees could be explained by the fact that these pollinators often rely on the complex visual signals of flowers to acquire food. For example, bees may need to memorize complex flower patterns to avoid deceptive plant flowers (Stejskal, Streinzer, Dyer, Paulus, & Spaethe, 2015). Interestingly, it has also been demonstrated that honeybees have the capacity to rely on configural processing with prolonged visual experience (Avarguès-Weber, Portelli, et al, 2010;Stach, Benard, & Giurfa, 2004;Stach & Giurfa, 2005), thus offering a fascinating parallel with primate visual processing (Avarguès-Weber et al, 2015).…”
mentioning
confidence: 99%
“…; Stejskal et al . ), we hypothesised that trait variance might differ between the two strategies. Generally, variation in sterile traits was found to be larger than variation of the fertile portions.…”
Section: Discussionmentioning
confidence: 99%